THE REPRESENTATION OF CERDIKIAWAN in GOJEK ADVERTISEMENT - Nabila Nabila; Yudha Asmara Dwi Aksa (Fakultas Komunikasi, Sastra, dan Bahasa, 2021)
Consistent communication is the main key in building and developing a business. In Indonesia, the phenomenon of startup business is growing rapidly. The increasingly fierce business competition makes each startup company competing with each other to promote their products, one of which is advertising. Advertising does not only function for the marketing of products or services, but in public memory so that it can add value to the brand because it has its own impression for those who see it. One of the startup company advertisements that not only attracts the attention of researchers but also the people of Indonesia is the Cerdikiawan version of Gojek Ads. This advertisement depicts the story of cerdikiawan. However, cerdikiawan word in this ad is a new word that has not been defined by the KBBI so that it doesn’t sounds familiar to the public. Plus the mention of the word cerdikiawan sounds similar to the word cendekiawan who clearly has been known and used longer. So that many people who interpret the concept of cerdikiawan are similar to cendekiawan. Therefore, this study aims to find out how the Smart Advertising version of the Smart Project represents the smart concept. Based on the simple definition presented by Gojek , cerdikiawan concept uses the analysis method of the semiotics theory by Charles Sanders Peirce's with his triadic triangles, that are sign, object, and interpretant. The selection of characters, settings, naration (seen words), the problem and how to solved in each scene become sign and object in producing interpreters about the representation of cerdikiawan. The results of this research explained that cerdikiawan is someone who has high creativity, unique, light–handed, and out of the box. Furthermore, cerdikiawan can be done by anyone, anytime, anywhere, and under any circumstances that are then equated with Gojek users.